IMPACT OF MACROECONOMIC INDICATORS ON FDI INFLOWS IN PRE & POSTIMPLEMENTATION OF MAKE IN INDIA - Dr. M. Sumathy,; Shallini. V, (EPRA International Journal of Research and Development (IJRD), 2023)
This study reveals the Foreign direct Investment inflows on macroeconomic indicators in Pre and Post of Make in India. The main objective of the study is to find the relationship between FDI inflows on macroeconomic indicators during pre and post of make in India and also analyse the impact of FDI on the Indian economy during pre and post of make in India. From the study period were segregated on the basis of pre and post of Make in India (2010 -11 to 2019-20). Augmented Dickey Fuller Unit Root Test is used for checking the stationarity of the Macroeconomic indicators. Correlation matrix is used to find the relationship between Foreign direct investment on macroeconomic variables during pre and post of Make in India proposal and Granger causalityis employed for the impact of Foreign direct Investment on macroeconomic indicators such as Balance of Payment, GDP, Exchange rate, inflation and export in pre and post of Make in India. The results show the strength of shows between the FDI inflows and exchange rate.The pairwise granger causality analysis of Foreign Direct Investment inflows and select macro-economic variables reveals the unidirectional casualty between the FDI and export in post Make in India implementation.